Agency and property rights theories in agricultural cooperatives: evidence from Spain - Minguez-Vera, A.; Martin-Ugedo, J. F.; Arcas-Lario, N. (Spanish Journal of Agricultural Research, 2010)
This manuscript examines the member-agricultural cooperative relationship from the point of view of the agency and the property rights theories. The sample analysed includes 277 personal surveys completed by members of agricultural cooperatives in the Region of Murcia (Spain). Results show that in all questions related to objectives and level of satisfaction, members value them with an average of 6.9 out of 10 or higher in all cases. For both objectives and satisfaction, the directors and the cooperative members who depend upon agricultural activity for a large percentage of their income have higher scores, compared with non-board members and members who are less dependent on agricultural activity (with a statistical significance of 1% and 5%, respectively). We also find that members who agree in more with the admission of new members, who think it is easy to recover their investments and who want to stay longer in the cooperative are those who are more willing to invest and to exert control. Furthermore, we find that members that prefer to have a participation in the assembly proportional to their contribution and that prefer that the cooperative diversifies more are those who are more willing to invest. In addition, control is favoured by members pertaining to the cooperative for a large period and for those members who think that investing in the cooperative is a high risk and who prefer long-term investments. Finally, directors are more willing to invest and to exert control.